Probability of winning and match length in Tiebreak Ten tennis - O`Donoghue, P.; Simmonds, E. (International Journal of Performance Analysis in Sport, 2019)
New formats of tennis have been developed to make matches more exciting and unpredictable than the traditional format of the game. The purpose of the current investigation was to compare the probability of winning between Tiebreak Ten matches and two other formats of the game; Fast4 tennis and traditional tennis. A probabilistic model of winning Tiebreak Ten tennis matches was created and compared with existing models of Fast4 and traditional tennis matches. This analysis was done for a full range of probabilities of players winning points when they are serving. This involved 100,000 simulations for each pair of probabilities for two players serving for multiple set matches in Fast4 tennis and traditional tennis. The probability of players beating higher ranked opponents was found to be higher in Tiebreak Ten matches than in Fast4 and traditional tennis matches. This confirms the claim that Tiebreak Ten matches are less predictable and hence more exciting than Fast4 and traditional tennis matches. KEYWORDS: Simulation, racket sports, rule changes, probability, modelling